Ultralow friction of ink-jet printed graphene flakes. Issue 22 (25th May 2017) - Buzio, R.; Gerbi, A.; Uttiya, S.; Bernini, C.; Del Rio Castillo, A. E.; Palazon, F.; Siri, A. S.; Pellegrini, V.; Pellegrino, L.; Bonaccorso, F.
Abstract : Nanofriction of ink-jet printed graphene flakes meets the benchmark set by cleaved graphene. Abstract : We report the frictional response of few-layer graphene (FLG) flakes obtained by the liquid phase exfoliation (LPE) of pristine graphite. To this end, we inkjet print FLG on bare and hexamethyldisilazane-terminated SiO2 substrates, producing micrometric patterns with nanoscopic roughness that are investigated by atomic force microscopy. Normal force spectroscopy and atomically-resolved morphologies indicate reduced surface contamination by solvents after a vacuum annealing process. Notably, the printed FLG flakes show ultralow friction comparable to that of micromechanically exfoliated graphene flakes. Lubricity is retained on flakes with a lateral size of a few tens of nanometres, and with a thickness as small as ∼2 nm, confirming the high crystalline quality and low defects density in the FLG basal plane. Surface exposed step edges exhibit the highest friction values, representing the preferential sites for the origin of the secondary dissipative processes related to edge straining, wear or lateral displacement of the flakes. Our work demonstrates that LPE enables fundamental studies on graphene friction to the single-flake level. The capability to deliver ultralow-friction-graphene over technologically relevant substrates, using a scalable production route and a high-throughput, large-area printing technique, may also open up new opportunities in the lubrication of micro- and nano-electromechanical systems.